Radio stars observed in the LAMOST spectral survey. (September 2017) - Zhang, Li-Yun; Yue, Qiang; Lu, Hong-Peng; Han, Xian-Ming L.; Zhang, Yong; Shi, Jian-Rong; Wang, Yue-Fei; Hou, Yong-Hui; Zi-Huang, Cao
Abstract: Radio stars have attracted astronomers' attention for several decades. To better understand the physics behind stellar radio emissions, it is important to study their optical behaviors. The LAMOST survey provides a large database for researching stellar spectroscopic properties of radio stars. In this work, we concentrate on their spectroscopic properties and infer physical properties from their spectra, such as stellar activity and variability. We mined big data from the LAMOST spectral survey Data Release 2 (DR2), published on 2016 June 30, by cross-matching them with radio stars from FIRST and other surveys. We obtained 783 good stellar spectra with high signal to noise ratio for 659 stars. The criteria for selection were positional coincidence within 1.5′′ and LAMOST objects classified as stars. We calculated the equivalent widths (EWs) of the Caii H&K, H δ, H γ, H β, H α and Caii IRT lines by integrating the line profiles. Using the EWs of the H α line, we detected 147 active stellar spectra of 89 objects having emissions above the H α continuum. There were also 36 objects with repeated spectra, 28 of which showed chromospheric activity variability. Furthermore, we found 14 radio stars emitting noticeably in the Caii IRT lines. The low value of the EW8542 /EW8498 ratio for these 14 radio stars possibly alludes to chromospheric plage regions.